Serum concentration of zinc is elevated in clinically stable bipolar disorder patients. Issue 1 (30th December 2021) - Jonsson, Bo H.; Orhan, Funda; Bruno, Sanna; Oliveira, Ana Osório; Sparding, Timea; Landen, Mikael; Sellgren, Carl M.
Abstract: Background: Bipolar disorder (BD) is a chronic psychiatric disorder characterized by recurrent mood episodes interspersed with euthymic periods. A growing number of studies have indicated that zinc plays an important role in coordinating immune responses, as well as being involved in synaptic transmission. In the current study, we set out to measure serum levels of zinc in a meticulously phenotyped cohort of 121 euthymic BD subjects and 30 matched controls. Methods: Serum levels of zinc were measured by photometry. To assess the interplay between zinc levels and immune activation in BD, we measured serum levels of high‐sensitive C‐reactive protein (hsCRP) levels by immunoturbidimetric assay, and serum levels of monocyte chemoattractant protein‐1 (MCP‐1), chitinase 3‐like protein 1 (YKL‐40), and soluble cluster of differentiation 14 (sCD14) by electrochemiluminescence enzyme‐linked immunosorbent assays. The baseline clinical diagnostic instrument for BD was the Affective Disorder Evaluation, and executive functioning was assessed by using the Delis–Kaplan Executive Function System. Results: Controlling for potential confounding factors, BD patients displayed increased serum levels of zinc unrelated to hsCRP, MCP‐1, YKL‐40, and sCD14 levels. Serum levels of zinc did not associate with executive functioning or measurements of disease severity. Discussion: This study suggests that the zinc homeostasis is disturbed in BD and that this dyshomeostasis is not related to ongoing mood symptoms or immune activation. Of note, serum levels were increased and hence do not support continuous zinc supplementation in BD. Abstract : Clinically stable bipolar disorder patients, compared to healthy matched controls, displayed elevated serum zinc levels unrelated to immune activation. Serum levels of zinc did not associate with executive functioning or measurements of disease severity.